2010
DOI: 10.1371/journal.pone.0012418
|View full text |Cite
|
Sign up to set email alerts
|

Mouse Gestation Length Is Genetically Determined

Abstract: BackgroundPreterm birth is an enormous public health problem, affecting over 12% of live births and costing over $26 billion in the United States alone. The causes are complex, but twin studies support the role of genetics in determining gestation length. Despite widespread use of the mouse in studies of the genetics of preterm birth, there have been few studies that actually address the precise natural gestation length of the mouse, and to what degree the timing of labor and birth is genetically determined.Me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
95
2

Year Published

2012
2012
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 129 publications
(112 citation statements)
references
References 12 publications
(17 reference statements)
7
95
2
Order By: Relevance
“…In our breeding colony controls, the cumulative death rate of offspring within 24 h of birth was 9% 6 3% and was comparable to previous reports for C57/B16 dams (5% 6 6%) [53]. Similarly, low offspring 24 h death rate was observed when dams were Gsk3a À/À b f/f (4% 6 2%) or oGsk3a þ/þ b À/À (5% 6 2%).…”
Section: Loss Of Oocyte Individual and Concomitant Gsk3 Isoforms And supporting
confidence: 89%
See 1 more Smart Citation
“…In our breeding colony controls, the cumulative death rate of offspring within 24 h of birth was 9% 6 3% and was comparable to previous reports for C57/B16 dams (5% 6 6%) [53]. Similarly, low offspring 24 h death rate was observed when dams were Gsk3a À/À b f/f (4% 6 2%) or oGsk3a þ/þ b À/À (5% 6 2%).…”
Section: Loss Of Oocyte Individual and Concomitant Gsk3 Isoforms And supporting
confidence: 89%
“…Inbred C57BL/6J and FVB/NJ mouse strains produce litters with 8 6 2 and 9 6 2 offspring, respectively [53]. Similarly, our mouse breeding colony produced 9 6 0.5 offspring/litter.…”
Section: Loss Of Oocyte Individual and Concomitant Gsk3 Isoforms And mentioning
confidence: 66%
“…We used a late-pregnancy model in C57Bl/6 mice. Gestation typically lasts 19±0.5 days in this strain 16 , so we chose day 18 as representative of late pregnancy (LP). Morphometric analysis showed that at day 18, an approximately 13% increase in heart weight to tibia length ratios (HW:TL) is observed (Figure 1A), consistent with what has been found in previous studies and indicative of physiological hypertrophy.…”
Section: Resultsmentioning
confidence: 99%
“…Gestational days 10.5, 12.5, and 14.5 for mouse pups seem to have particular implications on the offspring later in life, showing a wider range of ASD-like behaviors, such as more stereotypic behavior and less sociability (Bunting et al 2011). The typical gestational period for mice spans approximately 18-22 days (Murray et al 2010). Specifically, it appears that susceptibility during the second and third trimesters is critical to later atypical behavioral manifestation.…”
Section: Animal Analogues For Human Subjects With Asdmentioning
confidence: 99%